Response to Treatment with an Anti-Interleukin-6 Receptor Antibody (Tocilizumab) in a Patient with Hemophagocytic Syndrome Secondary to Immune Checkpoint Inhibitors - Alejandro Olivares-Hernández; Luis Figuero-Pérez; María A. Amores Martín; Lorena Bellido Hernández; Laura Mezquita; María del Rosario Vidal Tocino; Félix López Cadenas; Felipe Gómez-Caminero López; Roberto A. Escala-Cornejo; Juan Jesús Cruz Hernández (Case Reports in Oncological Medicine)
Background. Immunotherapy represents one of the fundamental treatments in the management of some types of cancer, especially malignant melanoma. Toxicity derived from increased immune system activity can manifest in multiple organs and systems. We present a case of hematological toxicity, manifested as hemophagocytic syndrome (HPS), which was successfully treated with an anti-interleukin-6 antibody (tocilizumab). Case Report. This case presents a 75-year-old woman diagnosed with metastatic choroidal melanoma, refractory to several lines of treatment. After the failure of the previous lines, ipilimumab was started. After the third dose, she developed grade 2 thrombocytopenia and anemia accompanied by elevated levels of ferritin, triglycerides, and decreased fibrinogen. Hemophagocytosis was observed in the bone marrow biopsy, and a PET-CT showed splenomegaly with increased metabolism. Treatment was based on high doses of corticosteroids and tocilizumab. Four days after the start of treatment, progressive clinical and analytical improvement was observed, achieving total remission of the condition. Discussion. HPS induced by immunotherapy is due to an immunorelated cytokine storm syndrome (CSS). The administration of the anti-interleukin-6 receptor antibody drug acted on this cytokine cascade, leading to stabilization and subsequent remission. For this reason, the use of tocilizumab should be part of the immunotherapy-induced HPS treatment algorithm.